2014
DOI: 10.1001/jamasurg.2013.3195
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation in Children Using Organ Donation After Circulatory Death

Abstract: Our study showed excellent long-term outcomes with liver transplantation in children using DCD organs. Use of liver grafts procured after circulatory death is an effective approach to expand the donor pool and remains an untapped resource for children with end-stage liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The safe utilization of pediatric DCD donors for LT has been shown recently with similar long-term outcomes as seen in the comparator DBD cohort. 29,88 Bartlett et al 89 presented the largest cohort from Kings College Hospital in London. In context of the potential donor and recipient age mismatch, there is a general reluctance to use DCD liver grafts for pediatric recipients.…”
Section: Recipient Agementioning
confidence: 99%
“…The safe utilization of pediatric DCD donors for LT has been shown recently with similar long-term outcomes as seen in the comparator DBD cohort. 29,88 Bartlett et al 89 presented the largest cohort from Kings College Hospital in London. In context of the potential donor and recipient age mismatch, there is a general reluctance to use DCD liver grafts for pediatric recipients.…”
Section: Recipient Agementioning
confidence: 99%
“…2,7 Notably, pDCD grafts have been even less utilization when compared to aDCD grafts. [8][9][10] As a result, the prognostic characteristics of pDCD grafts have not been fully established. As shown in this study, the majority of pDCD livers were allocated to adult recipients and the use of pDCD livers in pediatric recipients is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies for this type of donation have largely come from single-center case series or individual case reports. [8][9][10][11][12][13][14][15][16] It is also reported that the withdrawal of life-sustaining therapy (LST) accounts for around 30%-65% of deaths in pediatric intensive care. [17][18][19] Taken together, these findings suggest that pDCD liver donation has the potential to Original Clinical Science-Liver Background.…”
mentioning
confidence: 99%
“…In 2010, Hong et al from the University of California Los Angeles (UCLA) compared the long-term outcome of 7 children transplanted with DCD paediatric livers to that of 21 children transplanted with DBD paediatric grafts [ 23 ]. At 10-year follow-up, no graft or patient loss occurred in either group.…”
Section: The Use Of Donation After Circulatory Death Grafts In Paementioning
confidence: 99%
“…The DCD donors were all classified as Maastricht category III with a median donor age of 10 years (0.3 months–64 years) and a median donor WIT of 15 (10–25) minutes. Notably, the donor WIT was defined in 5 reports [ 20 23 , 25 ] as “the interval between post-withdrawal hypotension (systolic blood pressure < 50 mmHg) and the time of aortic perfusion with preservation solution,” while in 2 studies [ 18 , 26 ] it was defined as “the interval from withdrawal of life support to initiation of cold organ preservation.” In all DCD paediatric LT the donor “no touch” period was of 5 minutes from the declaration of death.…”
Section: The Use Of Donation After Circulatory Death Grafts In Paementioning
confidence: 99%